On dimension reduction for the power control problem. - Mendo, L.
We show how the dimension of power control equation systems can be reduced from K, the number of users in the system, to M, the number of cells, without any loss of generality or accuracy. Decentralized downlink power control algorithms are then presented which generalize previously proposed ones broadening the range of application while maintaining reduced complexity
Keywords: Cellular CDMA system; Code-division multiple access system; Decentralized downlink power control algorithms; Dimension reduction; Power control equation systems; Reduced complexity